Vulnerability in the health of young transgender women living with HIV/AIDS - Rafaela Greice da Silva; Paula Daniella de Abreu; Ednaldo Cavalcante de Araújo; Alef Diogo da Silva Santana; Josueida de Carvalho Sousa; Jorge Lyra; Claudia Benedita dos Santos (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to analyze the health vulnerability of young female transgender living with HIV/AIDS. Methods: qualitative, descriptive, and exploratory study, based on the theoretical reference of Social Representation and concept of vulnerability; developed with six transgender women in a reference Hospital for HIV/AIDS. We analyzed the individual interviews, recorded, and transcribed in full, in the IRaMuTeQ software by Similitude Analysis. Results: the thematic categories are listed based on the Ayres reference: 1) Individual dimension of vulnerability to HIV/AIDS; 2) Social dimension of vulnerability to HIV/AIDS; 3) Programmatic dimension of the vulnerability. Final Considerations: the young female transsexual living with HIV/AIDS experience a context of vulnerability in health associated with a lack of knowledge and difficulties for the realization of self-care. The study evidenced the representations of social abjection and unpreparedness of the health team that compose the Primary Attention in Health in promoting qualified assistance for the execution of the effective and humanized care.